2017
DOI: 10.1159/000460262
|View full text |Cite
|
Sign up to set email alerts
|

Femoral Neck X-Ray Absorptiometry Parameters and Peripheral Quantitative Computer Tomography Tibial Cortical Density Predict Survival in Dialysis Patients

Abstract: Background: Low bone mineral density (BMD) is a known independent predictor of mortality in the general elderly population. However, studies in patients with end-stage renal disease (ESRD) are limited. The present study evaluated mortality during long-term follow-up in a population of patients having dialysis for ESRD, in whom BMD was also measured. Methods: Fifty-eight patients with ESRD were recruited consecutively from a dialysis clinic and followed prospectively for 6 years. Baseline BMD of the lumbar spin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 57 publications
0
5
0
Order By: Relevance
“…This observation may indicate a stronger correlation with cortical bone-rich areas [ 32 ]. Additionally, cortical bone has also been linked to mortality, as evidenced by a five-year follow-up study in HD patients, which demonstrated that low BMD at the hip predicted mortality [ 33 , 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…This observation may indicate a stronger correlation with cortical bone-rich areas [ 32 ]. Additionally, cortical bone has also been linked to mortality, as evidenced by a five-year follow-up study in HD patients, which demonstrated that low BMD at the hip predicted mortality [ 33 , 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…Compared with the general population where there is an abundance of data, the relationship between BMD and CVD mortality in ESRD is less clear due to the relatively small number of patients and publications in this field. Most previous reports regarding ESRD patients analysed the association between BMD and all-cause mortality, while only a few studies investigated the relationship between BMD and CVD mortality in ESRD patients [ 6 , 7 , 17–20 , 66 , 67 ] ( Table 1 ).…”
Section: Low Bmd Predicts Increased All-cause and Cvd Mortalitymentioning
confidence: 99%
“…Furthermore, another study reported that forearm sites in addition to femoral neck were associated with high all-cause mortality in univariate analysis [ 19 ]. Yap et al [ 67 ] used pQCT in addition to DXA in a prospective study of 58 dialysis patients with 6 years follow-up and found that tibia cortical density by pQCT, in addition to BMD at femoral neck measured by DXA, was significantly associated with increased all-cause mortality.…”
Section: Low Bmd Predicts Increased All-cause and Cvd Mortalitymentioning
confidence: 99%
“…Finally, 12 studies were included in the review and meta-analysis. (12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23) Details of the literature search process are shown in Fig. 1.…”
Section: Characteristics Of Eligible Cohort Studiesmentioning
confidence: 99%
“…(14,16,17) The relationship between BMD at different sites and mortality risk is controversial in CKD patients. (12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23) Moreover, there are still no unique recommendations on the optimal sites for interpretation of bone loss and monitoring the prognosis of CKD patients. Thus, we aimed at conducting a systematic review and metaanalysis of cohort studies to evaluate the association of BMD at various bone sites with all-cause mortality in CKD patients.…”
Section: Introductionmentioning
confidence: 99%